2002
DOI: 10.1007/s00421-002-0685-2
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of electromyograph median frequency after lumbar muscle fatigue analysed using an exponential time dependence model

Abstract: The recovery of the median frequency of the power spectrum of the electromyogram (EMG) after fatigue has been studied to obtain reference data for healthy subjects (n = 55). In a seated position, the subjects performed a 45 s isometric back muscle contraction at 80% of maximal voluntary contraction, followed by 5 s contractions after 1, 2, 3, and 5 min in the recovery phase. In an additional reliability study (n = 11), this was performed six times. Surface EMG was recorded on four sites, namely, bilaterally fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 21 publications
(30 reference statements)
4
29
1
1
Order By: Relevance
“…Over the entire 1-h task we observed a cumulative increase in perceived fatigue and EMG amplitude but not a consistent decrease in the MPF, which is in line with several previous studies which have found that MPF recovery is fast after exercise (e.g. Elfving et al 2002).…”
Section: Development Of Fatiguesupporting
confidence: 91%
“…Over the entire 1-h task we observed a cumulative increase in perceived fatigue and EMG amplitude but not a consistent decrease in the MPF, which is in line with several previous studies which have found that MPF recovery is fast after exercise (e.g. Elfving et al 2002).…”
Section: Development Of Fatiguesupporting
confidence: 91%
“…When a subject rests after a fatiguing contraction, the median frequency measured from back and extremity muscles recovers to the initial level following an exponential curve function of time (Broman et al 1985;Kuorinka 1988;Vestergaard-Poulsen et al 1995;Alfonsi et al 1999;Elfving et al 2002). An exponential (non-linear) model is superior to models anticipating linearity in the analysis of metabolic changes during muscle contraction and recovery (Simond et al 2001).…”
Section: Introductionmentioning
confidence: 96%
“…12 Although intracellular acidosis is considered to contribute to muscle fatigue, it also plays a role in preserving excitability when depolarization occurs within the muscle during activity; that is, intracellular acidosis has a protective effect during muscle fatigue. 23 Considering recovery capacity (ie, a return to a nonfatigue condition 24 ) as an important tool in the analysis of neuromuscular function and low back pain, we also used REC to evaluate low back muscle performance in the present study. In contrast to our initial expectations, the results demonstrated higher values for MFr and, consequently, for REC in subjects with pain than in subjects without pain (Tabs.…”
Section: Low Back Pain Assessmentmentioning
confidence: 99%